Acute non-displaced fractures of the scaphoid: earlier return to activities after operative treatment : a controlled multicenter cohort study - Schädel-Höpfner, Michael; Marent-Huber, Marta; Gazyakan, Emre; Tanzer, Karin; Werber, Klaus D.; Siebert, Hartmut R. (Archives of orthopaedic and trauma surgery, 2010)
To investigate whether operative treatment leads to earlier return to previous activity level, 94 patients with the same number of isolated, acute, complete, stable and non-displaced fractures of the scaphoid mid-third were involved in a prospective, multicenter cohort study.
Erstmals am 17 November 2009 online veröffentlicht
Gesehen am 09.08.2023